'Ah, love! It's not for me!' Off-screen romance and Pola Negri's star persona. Issue 2 (3rd April 2017) - Frymus, Agata
ABSTRACT: The Polish actor Pola Negri embarked on her American film career in 1922, after signing a lucrative contract with Famous-Players Lasky. She was promoted as a fiery, European woman of temperament and 'a wild cat … who doesn't calculate'. Hollywood star discourse paid particular attention to romantic alliances between Negri and a number of successful screen actors; in generating this type of publicity, the studio ensured its chief star was portrayed as a passionate, continental diva. Yet the strategy proved to be a double-edged sword. First of all, the highly publicised, brief relationships with non-American men suggested a strong, active sexuality and unwillingness to settle down. Secondly, Negri's public disclosure of grief after the death of her fiancé Rudolph Valentino violated the more reserved American norms of mourning, attracting criticism. Her marriage to Prince Serge Mdivani shortly after Valentino's death caused outrage and reinforced her position as a star placed on the margins of the main current of American society. Fan magazines such as Photoplay ascribed Negri with the fixed, static persona of an Old-World diva, resistant to all attempts at Americanisation. As a result, Negri came to symbolise the most dreaded aspects of modernity in the person of the foreign woman, which effectively impeded the advancement of her Hollywood career.